2009
DOI: 10.3171/2009.3.jns081096
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal meningeal melanocytoma: a new pathological entity or the result of leptomeningeal seeding?

Abstract: Meningeal melanocytoma is a rare benign CNS tumor derived from the leptomeningeal melanocytes. Although unusual, malignant transformation with leptomeningeal seeding into the brain or spinal cord may occur years after the initial diagnosis. The authors report a unique case of multifocal benign meningeal melanocytoma involving both cerebellopontine angles and the thoracic spinal cord, with associated diffuse leptomeningeal hyperpigmentation. They review the literature relevant to this topic and discuss the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 24 publications
(28 reference statements)
1
41
1
1
Order By: Relevance
“…The tumor occurs almost exclusively in the posterior fossa and spinal cord. 6,7,10,11 The annual incidence of MM is estimated to be 1 case per 10 million people, and women are vulnerable. 10 Our hospital has an extremely large collection area for patients from Guangdong province and 4 neighboring provinces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor occurs almost exclusively in the posterior fossa and spinal cord. 6,7,10,11 The annual incidence of MM is estimated to be 1 case per 10 million people, and women are vulnerable. 10 Our hospital has an extremely large collection area for patients from Guangdong province and 4 neighboring provinces.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 These cells are present in the leptomeninges of healthy adults and may result in primary leptomeningeal pigmented tumors, including pigmented meningioma, malignant melanoma, MM, melanotic schwannoma, and melanoblastosis. 6,7 Malignant melanoma and MM are of the same origin and represent the malignant and benign ends of the tumor spectrum, respectively. 5 MM was first coined by Limas and Tio 3 in 1972.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate-grade melanocytic tumors are not easily classified as melanocytoma or melanoma as they present some histological features associated with aggressive behavior, and moreover, only sporadic cases have been reported in the literature (2,3). To the best of our knowledge, only two cases of multifocal primary melanocytic tumor have been reported in the literature (1,9). In this study, we present a case of multiple spinal cord melanoma located at the level of the cervical and upper thoracic vertebrae, and conduct a review of the pertinent literature.…”
Section: Introductionmentioning
confidence: 78%
“…Adjuvant radiation therapy and Gamma Knife radiosurgery have been shown to control tumor growth and improve outcome following partial resection (1, 12). Ali et al reported a case study of a 31-year-old patient presenting with a multifocal meningeal melanocytoma simultaneously affecting both cerebellopontine angles and the thoracic spinal cord, and exhibiting a remarkably aggressive clinical course and a poor prognosis (1). In this case study, we introduce a new entity, multiple intermediate-grade melanocytoma, which similarly appears to portend a poor prognosis.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation